Where Does Sexuality Come From? Sex and Institution: A Knot - Enrico Redaelli (EJP import test, 2020)
Summary: This essay analyzes the origin of sexuality and its relationship with the institution. The issue is addressed from the perspective of psychoanalysis (Freud, Lacan), anthropology (Claude Lévi-Strauss) and philosophy (Foucault, Butler, Zupančič, Žižek). From the analysis of sexual difference as “real/impossible” a perspective comes to light: sex it is not a symbolic construct and not even an extra-symbolic reference, but what marks the irreducible (contradiction) limit of the symbolic order.
Keywords: Butler; foucault; Freud; gender; institution; Lacan; lévi-strauss; Nature-culture Divide; sex; Žižek; Zupančič